2022
DOI: 10.3389/fpsyt.2022.939707
|View full text |Cite
|
Sign up to set email alerts
|

Chronic tobacco smoking, impaired reward-based decision-making, and role of insular cortex: A comparison between early-onset smokers and late-onset smokers

Abstract: IntroductionThe literature suggests that tobacco smoking may have a neurotoxic effect on the developing adolescent brain. Particularly, it may impair the decision-making process of early-onset smokers (<16 years), by rendering them more prone to impulsive and risky choices toward rewards, and therefore more prone to smoking relapses, in comparison to late-onset smokers (≥16 years). However, no study has ever investigated reward-based decision-making and structural brain differences between early-onset s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…No correlations were identified between tobacco use/exposure characteristics and GM/WM volume of early-onset smokers' anterior insular cortex. As reported in our previous study, this may indicate that such structural abnormalities were not due to differences in tobacco exposure between the two groups ( 31 ).…”
Section: Structural Differences In the Insular Cortex Between Early-o...supporting
confidence: 85%
See 3 more Smart Citations
“…No correlations were identified between tobacco use/exposure characteristics and GM/WM volume of early-onset smokers' anterior insular cortex. As reported in our previous study, this may indicate that such structural abnormalities were not due to differences in tobacco exposure between the two groups ( 31 ).…”
Section: Structural Differences In the Insular Cortex Between Early-o...supporting
confidence: 85%
“…Recently, we conducted a VBM study hypothesizing that 11 adult smokers (mean age at recruitment = 25.2 years) who started regular tobacco use at 13.2 years of age (i.e., early-onset smokers) would present heightened impulsive and risky choices, in addition to reduced GM and WM volume in frontal brain regions modulating such behaviors in comparison with 17 adult smokers (mean age at recruitment= 30 years) who started regular smoking at 18 years of age (i.e., late-onset smokers) and 24 matched non-smoker controls ( 31 ). Our hypotheses were based on the previously cited TINACD theory ( 11 ).…”
Section: Structural Differences In the Insular Cortex Between Early-o...mentioning
confidence: 99%
See 2 more Smart Citations
“…Nicotine, a key component found in tobacco and electronic cigarettes, intricately engages with the developing brain primarily through its interaction with nicotinic acetylcholine receptors (nAChRs) crucial for regulating cognitive and neural functions, potentially resulting in changes at both structural and functional levels [ 56 , 57 , 58 ]. Prior research has shown that nicotine exposure during this adolescent and emerging adult developmental phase can influence neural plasticity and neurotransmitter systems, potentially leading to modifications in gray matter integrity, white matter development, and cortical thickness [ 27 , 29 , 59 , 60 , 61 ]. Our findings, showing thinner cortical estimates in regions such as the right precentral gyrus, left superior frontal gyrus, left pars opercularis, and left frontal pole among nicotine users, may reflect deleterious alterations in neuromaturation.…”
Section: Discussionmentioning
confidence: 99%